2015
DOI: 10.1159/000371549
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hypothyroidism on Color Contrast Sensitivity: A Prospective Study

Abstract: group after euthyroidism was achieved, which denotes improvement in color contrast sensitivity. Conclusions: It is a novel finding of the current study that color contrast sensitivity is impaired in hypothyroidism and significantly improves after euthyroidism is achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 23 publications
3
16
2
Order By: Relevance
“… 19 who, for the first time, showed that M-opsin expression is still prone to TH manipulation in fully maturated photoreceptors of adult mice and rats. A similar effect was reported in adult hypothyroid human patients treated with T4, based on a colour contrast sensitivity test 25 . It can be argued that the contradicting observation is a consequence of prolonged natural TH deprivation experienced by the mole-rat retina.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“… 19 who, for the first time, showed that M-opsin expression is still prone to TH manipulation in fully maturated photoreceptors of adult mice and rats. A similar effect was reported in adult hypothyroid human patients treated with T4, based on a colour contrast sensitivity test 25 . It can be argued that the contradicting observation is a consequence of prolonged natural TH deprivation experienced by the mole-rat retina.…”
Section: Discussionsupporting
confidence: 78%
“…This suppresses S-opsin expression and instead activates M-opsin expression 17 , 23 , 24 . Low serum TH levels, a state referred to as hypothyroid, thus leads to downregulation of M-opsin expression with a high plasticity throughout adulthood, at least in mice, rats, and likely also in humans 19 , 25 . Interestingly, we have previously shown that Ansell’s mole-rats have serum FT4 levels which are approximately 10-fold lower compared to other rodents, while FT3 levels are in the rodent-typical range 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Primary hypothyroidism has signi cantly increased the risk of open-angle glaucoma [14] , which eventually results in visual eld defects [15] . Additionally, hypothyroidism has a high incidence of color contrast sensitivity impaired [16] and visual evoked potential (VEP) disorders [17], [18] . Higher baseline thyroid-stimulating hormone could be associated with faster cognitive decline over-time among US adults in the urban area, speci cally in domains of working memory and visuospatial and/or vasoconstriction abilities [19] .…”
Section: Introductionmentioning
confidence: 99%
“…The iris enables the eye for adapting the lightness levels, where the retina is lightsensitive and the vision of color is possible only for up to 40° angles around the optical axis, in fact, the human cannot differentiate colors at low light [2]. The effect of color vision is prominent in human, and in particular, the effect on color contrast sensitivity [3]. Color effects in the human brain and psychology such as behavior, activities, and studies.…”
Section: Introductionmentioning
confidence: 99%